Kepentingan Jepang Dalam Proyek Kereta Cepat Mumbai-Ahmedabad di India - Kusuma Riandra, Ni Nyoman Indira Tri; Sushanti, Sukma; Nugraha, A.A. Bagus Surya (Program Studi Hubungan Internasional FISIP Universitas Udayana, 2021)
This study describes Japan’s interest in the construction of the Mumbai-Ahmedabad high-speed train in India using qualitative research methods. This study uses two concepts, at first, the of Japanese national interest which explains that in making a country’s policy based on the interests of a country and the concept of stagflation which sees the success of the policies made by the Japanese Prime Minister in achieving their national interest. The results of this research show that the benefits for Japan on the Mumbai-Ahmedabad high-speed rail project are to overcome Japanese stagflation and threats from China. Key Words: Quality Infrastructure, Official Development Assistance, Belt and Road Initiative, Bullet Train.